Mineral composition of the red currant (Ribes rubrum L.) variety Redpoll lyophilized waste extract - Cvetković, Maja; Ilić, Dušan; Petrović, Sanja; Miladinović, Bojana (Archives of Pharmacy, 2022)
Red currants are berries appreciated for their characteristic aroma, trendy shape and numerous health benefits. They are abundant in sugars and phytonutrients. Red currants are also an excellent source of minerals. According to the literature, red currants are especially rich in potassium, calcium and magnesium. The aim of this study was to determine the contents of mineral elements in lyophilized waste extract obtained from red currant variety Redpoll (Ribes rubrum L.), in order to evaluate its possible applications. The analysis included the determination of 22 chemical elements. Sample preparation was performed by wet digestion, after which the concentration of elements was determined by inductively coupled plasma - optical emission spectrometry (ICP-OES). The mineral composition is shown by decreasing concentrations: K